Pengembangan Kurikulum Pendidikan Agama Islam yang Relevan dengan Tantangan Kontemporer - Sari Butar Butar, Fadilah; Pani, Pani; Sari, Dina (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2024)
Islamic Religious Education is an essential component within the education system, playing a crucial role in shaping values, morality, and the character of learners. However, facing the ever-changing dynamics of the times, contemporary challenges such as technological advancements, globalization, pluralism, and social changes demand adaptation and readiness of the curriculum to be relevant and responsive to current needs. This paper explores the importance of developing an curriculum that accommodates and responds to these challenges, ensuring that the curriculum provides relevant and meaningful learning in the context of an ever evolving era. The discussion focuses on adjusting curriculum content, innovative teaching methods, and emphasizing character education within the curriculum that aligns with contemporary challenges. Furthermore, an analysis is conducted on the challenges in the curriculum development process, such as limited resources, resistance to change, and strategies to overcome these obstacles.